Magnetotactic Coccus Strain SHHC-1 Affiliated to Alphaproteobacteria Forms Octahedral Magnetite Magnetosomes - Zhang, Heng; Menguy, Nicolas; Wang, Fuxian; Benzerara, Karim; Leroy, Eric; Liu, Peiyu; Liu, Wenqi; Wang, Chunli; Pan, Yongxin; Chen, Zhibao; Li, Jinhua (Frontiers in Microbiology, 2017)
Magnetotactic bacteria (MTB) are morphologically and phylogenetically diverse prokaryotes. They can form intracellular chain-assembled magnetite (Fe3O4) or greigite (Fe3S4) nanocrystals each enveloped by a lipid bilayer membrane called a magnetosome. Magnetotactic cocci have been found to be the most abundant morphotypes of MTB in various aquatic environments. However, knowledge on magnetosome biomineralization within magnetotactic cocci remains elusive due to small number of strains that have been cultured. By using a coordinated fluorescence and scanning electron microscopy method, we discovered a unique magnetotactic coccus strain (tentatively named SHHC-1) in brackish sediments collected from the estuary of Shihe River in Qinhuangdao city, eastern China. It phylogenetically belongs to the Alphaproteobacteria class. Transmission electron microscopy analyses reveal that SHHC-1 cells formed many magnetite-type magnetosomes organized as two bundles in each cell. Each bundle contains two parallel chains with smaller magnetosomes generally located at the ends of each chain. Unlike most magnetotactic alphaproteobacteria that generally form magnetosomes with uniform crystal morphologies, SHHC-1 magnetosomes display a more diverse variety of crystal morphology even within a single cell. Most particles have rectangular and rhomboidal projections, whilst others are triangular or irregular. High resolution transmission electron microscopy observations coupled with morphological modeling indicate an idealized model - elongated octahedral crystals, a form composed of eight {111} faces. Furthermore, twins, multiple twins and stack dislocations are frequently observed in the SHHC-1 magnetosomes. This suggests that biomineralization of strain SHHC-1 magnetosome might be less biologically controlled than other magnetotactic alphaproteobacteria. Alternatively, SHHC-1 is more sensitive to the unfavorable environments under which it lives, or a combination of both factors may have controlled the magnetosome biomineralization process within this unique MTB.